The Effectiveness of Learning Process and Outcome Assessment Based on The Hijaiyah Letter Tree Media in Improving Early Literacy Skills of Early Childhood - Ilmayanti, Linda; Alfauzan Amin (PT Inovasi Pratama Internasional, 2026)
Learning the hijaiyah letters in early childhood is an important foundation in the development of religious literacy, so creative and fun methods are needed to increase children's interest in learning. This study focuses on the effectiveness of the Hijaiyah Letter Tree media in improving the ability of PAUD children in recognizing, naming, and attaching hijaiyah letters through a playful approach. The purpose of this study is to describe the learning process using this media, assess the development of children's abilities, and identify supporting factors and obstacles during the activity. This study also provides benefits for teachers, children, institutions, and parents in strengthening hijaiyah learning in an integrated manner. The research method used is descriptive qualitative with a Classroom Action Research (CAR) model. The research subjects consisted of 15 children from group B PAUD Pembina, Karang Jaya District. Data were collected through observation, documentation, and formative assessment, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Hijaiyah Letter Tree media is effective in increasing children's attention, motivation, and ability to recognize and pronounce hijaiyah letters. Most children were able to display good learning performance, while some children required further assistance, especially in aspects of pronunciation and learning focus. The visual, verbal, and kinesthetic activities combined in this medium contribute to increased child engagement during the learning process. In conclusion, the Hijaiyah Letter Tree can be used as an alternative learning medium that is effective, interactive, and appropriate for the developmental characteristics of early childhood. Reinforcement through parental involvement is essential to maintain consistent learning at home.